Use of anti-tuberculosis drugs among newly diagnosed pulmonary tuberculosis inpatients in China: a retrospective study. Issue 1 (December 2016) - Huang, Fei; Zhang, Hui; Lv, Qing; Sato, Kaori; Qu, Yan; Huan, Shitong; Cheng, Jun; Zhao, Fei; Wang, Lixia
Abstract Background China's national tuberculosis control program (NTP) provides free, first-line anti-tuberculosis (TB) drugs to pulmonary TB patients. This treatment regimen follows the World Health Organization's (WHO) guideline. The objective of this paper is to evaluate the current status of anti-TB drug use for newly diagnosed pulmonary TB inpatients treated in prefecture- and county-level designated hospitals. Methods Three prefecture-level hospitals and nine county-level hospitals were selected for the study. All newly diagnosed pulmonary TB inpatient medical records from 2012 were reviewed and doubly examined by two national senior physicians. The rational use of anti-TB drugs was evaluated based on criteria in line with WHO's guideline. Results Of the 2, 060 total treatment regimens for TB, 53.1 % were found to be rational (1093/2060). The percentages in prefecture-level and county-level hospitals were 50.3 % (761/1513) and 60.7 % (332/547), respectively. The difference between the two levels of hospitals was statistically significant (Chi-square value = 17.44, P  < 0.01). The percentages of rational treatment regimens for first-time hospitalizations and for two or more hospitalizations were 59.5 % (983/1653) and 27.0 % (110/407), respectively, with a statistically significant difference (Chi-square value = 138.00, P  < 0.01). The overall use of second-line drugs (SLD) was 54.9 % (1131/2060). The percentages for prefecture-level and county-level hospitals were 50.6 % (766/1513) and 66.7 % (365/547), respectively. A statistically significant difference was found (Chi-square value = 42.06, P  < 0.01). The use of SLD for inpatients hospitalized once and inpatients hospitalized twice or more was 58.4 % (966/1653) and 40.5 % (165/407), respectively, with a statistically significant difference (Chi-square value = 42.26, P  < 0.01). Conclusions Half of inpatients might be treated with irrational regimens, and the use of SLD was more appropriately dispensed in city-level hospitals than in county-level hospitals. Trainings and guidelines for health personnel, supervision led by health authorities and increased investment to designated hospitals may help to improve the rational use of anti-TB drugs.